Catalyst for fuel cell and preparation method thereof

By using a combination of porous carbon support, platinum complex and sulfur-containing ligand in fuel cell catalysts, the S-C metal anchor anchor positioning point and Pt-S bond are formed, which solves the problem of poor catalyst stability and achieves high activity and high durability The platinum carbon catalyst reduces the operating cost of the fuel cell system.

CN119481092APending Publication Date: 2025-02-18ZHEJIANG TIANNENG HYDROGEN ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411479971.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing carbon-loaded platinum catalysts have poor stability and are easily contaminated by impurities and corrosion by carbon, resulting in a decrease in the electrochemical active surface area of ​​the fuel cell catalytic layer, affecting the performance of membrane electrodes and system operating costs.

Method used

Porous carbon is used as a support, and the S-C metal anchor positioning point is formed through the cooperation of platinum complex and sulfur-containing ligand, which enhances the dispersion of platinum on the support, and forms Pt-S bonds during high-temperature reduction to avoid platinum nanometers. Aggregation and sintering of particles.

Benefits of technology

It improves the durability and activity of the catalyst, extends the service life of the fuel cell, and reduces the system operation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481092A_ABST
    Figure CN119481092A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for a fuel cell and a preparation method thereof, a platinum complex is used as a precursor of metal platinum, the reducibility of a complex ligand dimethyl glyoxime under a high-temperature condition is utilized, platinum nanoparticles with controllable particle size are prepared through high-temperature pyrolysis reduction, hydrogen needed by conventional thermal reduction is not needed, and the catalyst is simple in preparation process and low in cost. The operation is safe and reliable; porous carbon is adopted and subjected to vacuum high-temperature treatment, an appropriate pore structure is beneficial to diffusion of a metal precursor, after a small-molecule solvent is adopted, the metal precursor can be evenly distributed on the surface of the carrier and in pores, the proportion of platinum in the pores is large, and the pores can play a certain confinement role in the accelerated aging process; in addition, an S-C metal anchoring site is formed by adding the sulfur element, so that the dispersity of platinum on the carrier is enhanced; according to the soft and hard acid-base principle, Pt-S bonds have strong interaction, and agglomeration and sintering of platinum nanoparticles in the heat treatment process are avoided through formation and elimination of the Pt-S bonds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy materials, and in particular to a catalyst for a fuel cell and a preparation method thereof. Background Art

[0002] A hydrogen fuel cell is a power generation device that converts the chemical energy of hydrogen directly into electrical energy. Due to its unique mechanism, it has obvious advantages: 1. High energy density. Hydrogen is a substance with a high energy density, and its calorific value is about 3 times that of gasoline; 2. Environmentally friendly, the exhaust gas is only water; 3. High conversion efficiency, and its combined heat and power efficiency is as high as 80%; 4. Low noise. Compared with many dynamic components of thermal engines, fuel cells are quieter as a power output source. Proton exchange membrane fuel cells are fuel cells with solid proton exchange membranes as electrolytes, and have broad application prospects. The membrane electrode is a core component obtained by hot pressing the gas diffusion layer after the anion and cation catalysts are sprayed on both sides of the proton exchange membrane; the platinum-based catalyst is the core component of the membrane electrode, and its performance directly affects the output performance of the membrane electrode; in addition, due to the scarcity of platinum resources, mass production cannot lead to a reduction in its price, and the platinum catalyst will always be the bulk of the cost of the stack.

[0003] The patent application with publication number CN117317250A provides a method for improving the durability of platinum-based catalysts; the method comprises the following steps: ultrasonically dispersing a platinum-carbon catalyst having a certain platinum content in water to obtain a mixture dispersion A; adding a mixed solution of citric acid and urea to the dispersion A according to a stoichiometric ratio, mixing evenly, and obtaining a mixture dispersion B; transferring the mixed dispersion B into a hydrothermal reactor, and continuing to keep warm at 120 to 200° C. for several hours; and finally, filtering, washing, drying, and screening to obtain a platinum-carbon catalyst modified with graphene quantum dots.

[0004] The invention patent with application number CN202210265874.4 provides a bifunctional modified platinum-carbon catalyst and a preparation method thereof, wherein the bifunctional groups are nitrogen doping and amino modification, and relate to the field of fuel cells. The preparation method comprises: obtaining a carbon carrier with N-doping and NH2 group modification on the surface. The modified carbon carrier is uniformly dispersed in a reducing agent to form a suspension, the suspension is mixed with a platinum salt precursor solution and subjected to a reduction reaction, so that the platinum ions are reduced to platinum element and loaded on the surface of the modified carbon carrier, followed by centrifugation, filtration, and drying to obtain a first powder. After the first powder is encapsulated by recrystallization and solidification of an inert inorganic salt, it is annealed at 300-600°C for 1-3h to obtain a second powder coated with an inert inorganic salt layer on the surface, and the inert inorganic salt layer is removed. The bifunctional modified platinum-carbon catalyst provided by the invention can effectively improve the activity and durability of the prepared platinum-carbon catalyst.

[0005] Platinum-based catalysts are prone to attenuation during use and may be contaminated by impurities from the reactant supply system. During operation, the agglomeration or migration of Pt particles on the carbon support will reduce the electrochemically active surface area (ECSA). Pt particles may also separate from the carbon support and dissolve in the ionic polymer phase. Ultimately, the carbon support is also prone to degradation, which is called carbon corrosion. The above results will lead to a decrease in the ECSA of the fuel cell catalyst layer, thereby affecting the membrane electrode performance and increasing the operating cost of the fuel cell system. Therefore, the development of highly active and durable platinum-based catalysts is one of the important methods to achieve the goal of low platinum in fuel cells. Summary of the invention

[0006] The purpose of the present invention is to provide a catalyst for a fuel cell and a preparation method thereof in view of the poor stability of existing carbon-supported platinum catalysts, so as to achieve the preparation of a highly active and durable catalyst.

[0007] In order to achieve the above-mentioned purpose, the specific technical scheme of the present invention is as follows:

[0008] In one aspect, the present invention provides a method for preparing a fuel cell catalyst, wherein the carrier of the fuel cell catalyst is porous carbon, the active component is metal platinum, and the loading amount of the metal platinum is 40wt% to 60wt%; the preparation method comprises the following steps:

[0009] (1) dissolving a platinum complex in an organic solvent to prepare a platinum salt precursor solution;

[0010] (2) mixing and uniformly dispersing a platinum salt precursor solution, porous carbon, a sulfur-containing ligand, and an organic solvent, and reacting the mixture to obtain a mixed solution;

[0011] (3) removing the solvent from the mixed liquid to obtain a solid, and reducing the solid under high temperature and reducing gas to obtain the fuel cell catalyst.

[0012] Preferably, in step (1), the platinum complex is at least one of dimethylglyoxime platinum complex and dimethylphosphonic acid platinum complex, the organic solvent is at least one of ethanol, isopropanol and n-propanol, and the concentration of the platinum salt precursor solution is 2wt%-20wt%. In the embodiment of the present invention, the concentration of the platinum salt precursor solution is selected as 10wt% as an example, but is not limited thereto.

[0013] The dimethylglyoxime platinum complex is obtained by using dimethylglyoxime as a ligand to react with a platinum salt to form a coordination reaction;

[0014] The dimethylglyoxime platinum complex is prepared from dimethylglyoxime, ethanol, polyethylene glycol and platinum salt. Because it is not suitable for long-term storage, it is generally prepared and used immediately. In the embodiment of the present invention, as an example, the main method is to dissolve dimethylglyoxime in an ethanol solution, then add a potassium chloroplatinate aqueous solution and polyethylene glycol at a temperature of 60°C, mix and stir for a certain period of time, wash, and then dry to obtain the desired dimethylglyoxime platinum complex;

[0015] The dimethylphosphonic acid platinum complex is a (dimethylphosphonic acid) platinum (II) hydrogenated complex.

[0016] Specifically, in step (2), the porous carbon is any one of the following commercial carbons: NCP-50, NCP-20-HT and NCP-50HT, which has a large number of pores, the surface pores are connected to the spherical pores below, and the interior is a three-dimensionally connected spherical channel structure, which is suitable for the loading of platinum nanoparticles;

[0017] The sulfur-containing ligand is at least one of 2-2-bithiophene, diphenyl sulfoxide and disulfide. 2-2-bithiophene, diphenyl sulfoxide and disulfide all contain sulfur atoms and can provide sulfur elements for the catalyst to form SC metal anchoring sites and enhance the dispersion of platinum on the carrier. In the embodiment of the present invention, 2-2-bithiophene is selected as an example. Based on the above mechanism, the other two sulfur-containing ligands can also achieve the above effect.

[0018] The organic solvent is at least one of ethanol, isopropanol, acetone and N,N-dimethylformamide;

[0019] The mass ratio of the porous carbon to the organic solvent is 1:10-100. In the embodiment of the present invention, the mass ratio of the porous carbon to the organic solvent is 1:50 as an example;

[0020] The mass ratio of platinum in the platinum salt precursor solution to sulfur in the sulfur-containing ligand is 1:1-20. In the embodiment of the present invention, the mass ratio of platinum to sulfur is 1:1-10 as an example.

[0021] The present invention uses a sulfur-containing ligand, and forms SC metal anchoring sites by adding sulfur elements in the sulfur-containing ligand, thereby enhancing the dispersibility of platinum on the carrier; according to the soft and hard acid-base principle, there is a strong interaction between Pt-S bonds, and the formation and elimination of Pt-S bonds can avoid the agglomeration and sintering of platinum nanoparticles during the heat treatment process.

[0022] Preferably, in step (2), the porous carbon is pretreated before use, and the pretreatment is: vacuum drying at a drying temperature of 150-250° C. for 12-48 hours. The main function of vacuum drying before the porous carbon reacts with the platinum precursor solution is to remove moisture, accelerate the drying process, maintain material properties and improve the reaction quality.

[0023] Preferably, in step (2), the dispersion is carried out by ultrasonic dispersion, the frequency of the ultrasonic dispersion is 30-60 KHZ, and the ultrasonic time is 30-180 min. In the embodiment of the present invention, the ultrasonic frequency is preferably 50 KHZ.

[0024] In some embodiments of the present invention, in step (3), the specific steps of removing the solvent in the mixed solution to obtain a solid are: placing the mixed solution in a rotary evaporator, evaporating the solvent in the mixed solution by heating in a water bath, and obtaining a solid;

[0025] The temperature of the water bath is 60-90° C., and the rotary evaporation rate of the rotary evaporator is 300-900 rpm.

[0026] In some embodiments of the present invention, in step (3), the solid is reduced under high temperature and reducing gas. During the reduction, the reducing gas used is a mixed gas of hydrogen and argon, wherein the volume ratio of hydrogen to the mixed gas is 5%.

[0027] During the reduction process, ventilation was continued at a flow rate of 50-200 ml / min;

[0028] The reduction temperature is 300-900°C, the reduction time is 0.5-3h, and the heating rate is 5-15°C / min.

[0029] With the change of sulfur content and reduction temperature, the platinum particle size tends to increase. This shows that during the gas phase preparation process, sulfur can slow down the agglomeration of platinum nanoparticles, but the amount cannot be too much; if the reduction temperature is too high, the sulfur element on the carrier may be completely removed, thereby losing the function of anchoring the platinum nanoparticles.

[0030] In some embodiments of the present invention, in step (3), the solid is reduced under high temperature and reducing gas, washed with water, and then filtered and dried to obtain the fuel cell catalyst;

[0031] The drying temperature is 60-100° C., and the drying time is 2-6 hours.

[0032] On the other hand, the present invention also provides a fuel cell catalyst prepared by the preparation method.

[0033] The present invention adopts porous carbon and undergoes vacuum high-temperature treatment. The suitable pore structure is conducive to the diffusion of metal precursors. After using small molecule solvents, the metal precursors can be evenly distributed on the surface of the carrier and in the pores, and the platinum accounts for a relatively large proportion in the pores. In the accelerated aging process, the pores can play a certain limiting role, coupled with the anchoring effect of sulfur on the carrier, the synergistic effect improves the durability of the catalyst. The data in the embodiments show that after 10,000 cycles of accelerated aging, the attenuation rates of Example 3, Comparative Example 1 and Comparative Example 2 are 35.8%, 58.2% and 60.8%, respectively.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. Platinum complex is used as the precursor of metal platinum. The reducibility of the complex ligand dimethylglyoxime under high temperature conditions is utilized to prepare platinum nanoparticles with controllable particle size through high-temperature pyrolysis reduction. There is no need to use hydrogen required for conventional thermal reduction, and the operation is safe and reliable.

[0036] 2. Porous carbon is used as a catalyst carrier, carbon black is dispersed through small molecule solvents such as ethanol, acetone, DMF, etc., a platinum precursor is introduced into the porous carbon, and in-situ reduction is performed to increase the distribution ratio of platinum inside and outside the pores; SC metal anchoring points are formed by adding sulfur elements to enhance the dispersion of platinum on the carrier; according to the principle of soft and hard acids and bases, there is a strong interaction between Pt-S bonds, and the formation and elimination of Pt-S bonds can avoid the agglomeration and sintering of platinum nanoparticles during heat treatment; through the improvement of the preparation process of the present invention, a highly durable platinum-carbon catalyst is prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 XRD test patterns of the catalysts prepared in Examples 1-6;

[0038] Figure 2 XRD test patterns of the catalysts prepared in Comparative Example 1 and Comparative Example 2;

[0039] Figure 3 Electrochemical test spectra of the catalysts prepared in Examples 1-6;

[0040] Figure 4 Electrochemical test spectra of the catalysts prepared in Comparative Example 1 and Comparative Example 2;

[0041] Figure 5 Electrochemical test spectra of the catalyst prepared in Example 3 before and after accelerated aging;

[0042] Figure 6 Electrochemical test spectra of the catalyst prepared in Comparative Example 1 before and after accelerated aging;

[0043] Figure 7This is the electrochemical test spectrum of the catalyst prepared in Comparative Example 2 before and after accelerated aging. DETAILED DESCRIPTION

[0044] The dimethylglyoxime platinum complex used in the present invention is prepared from dimethylglyoxime, ethanol, polyethylene glycol and platinum salt. Because it is not suitable for long-term storage, it needs to be prepared and used immediately. In the embodiment of the present invention, as an example, the method is: dissolve dimethylglyoxime in an ethanol solution to obtain a 0.1M ethanol dimethylglyoxime solution, take 20ml of 0.1mol / L ethanol dimethylglyoxime solution, then add 10ml of 0.05mol / L potassium chloroplatinate aqueous solution and 5ml polyethylene glycol at a temperature of 60°C, mix and stir for a certain period of time, wash, and then dry to obtain the desired dimethylglyoxime platinum complex.

[0045] Example 1

[0046] Dissolve dimethylglyoxime platinum complex in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, weigh 2.63g of 10wt% dimethylglyoxime platinum complex precursor solution, 0.1g NCP-50 carbon black (pre-treated by vacuum drying at 200 degrees for 24 hours) in a beaker, add 5g acetone, 0.112g 2-2-bithiophene (sulfur to platinum mass ratio is 1:2.5), 50KHZ ultrasonic dispersion for 60 minutes, and stir at room temperature overnight; then transfer the mixed solution to a rotary evaporator flask, set the water bath temperature to 70°C, and evaporate the solvent at 450rpm; then place the solid in a quartz boat, and continuously pass 100ml / min 5% H2 / Ar (hydrogen accounts for 5% of the volume ratio of the mixed gas) reducing gas, then the temperature is increased to 700°C at a heating rate of 5°C / min, high-temperature reduction is carried out for 2 hours, and then the temperature is naturally cooled under ventilation conditions; the catalyst is then washed with deionized water, filtered, and finally dried in an air drying oven at 70°C for 12 hours to obtain the desired catalyst.

[0047] Example 2

[0048] Dissolve dimethylglyoxime platinum complex in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, weigh 2.63g of the 10wt% dimethylglyoxime platinum complex precursor solution, 0.1g of NCP-50 carbon black (pre-treated by vacuum drying at 200 degrees for 24 hours) in a beaker, add 5g of acetone, 0.056g of 2-2-bithiophene (the mass ratio of sulfur to platinum is 1:5), 50KHZ ultrasonic dispersion for 60 minutes, and stir at room temperature overnight; then transfer the mixed solution to a rotary evaporator flask, set the water bath temperature to 70°C, and evaporate the solvent at 450rpm; then place the solid in a quartz boat, and continuously pass 100ml / min 5% H2 / Ar reducing gas was used, and then the temperature was raised to 700°C at a heating rate of 5°C / min, and high-temperature reduction was performed for 2 hours, followed by natural cooling under ventilation conditions; the catalyst was then washed with deionized water, filtered, and finally dried in an air drying oven at 70°C for 12 hours to obtain the desired catalyst.

[0049] Example 3

[0050] Dissolve dimethylglyoxime platinum complex in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, weigh 2.63g of 10wt% dimethylglyoxime platinum complex precursor solution, 0.1g NCP-50 carbon black (pre-treated by vacuum drying at 200 degrees for 24 hours) in a beaker, add 5g acetone, 0.028g 2-2-bithiophene (mass ratio of sulfur to platinum is 1:10), 50KHZ ultrasonic dispersion for 60 minutes, and stir at room temperature overnight; then transfer the mixed solution to a rotary evaporator flask, set the water bath temperature to 70°C, and evaporate the solvent at 450rpm; then place the solid in a quartz boat, and continuously pass 100ml / min 5% H2 / Ar reducing gas was used, and then the temperature was raised to 700°C at a heating rate of 5°C / min, and high-temperature reduction was performed for 2 hours, followed by natural cooling under ventilation conditions; the catalyst was then washed with deionized water, filtered, and finally dried in an air drying oven at 70°C for 12 hours to obtain the desired catalyst.

[0051] Example 4

[0052] Dissolve dimethylglyoxime platinum complex in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, weigh 2.63g of 10wt% dimethylglyoxime platinum complex precursor solution, 0.1g NCP-50 carbon black (pre-treated by vacuum drying at 200 degrees for 24 hours) in a beaker, add 5g acetone, 0.028g 2-2-bithiophene (mass ratio of sulfur to platinum is 1:10), 50KHZ ultrasonic dispersion for 60 minutes, and stir at room temperature overnight; then transfer the mixed solution to a rotary evaporator flask, set the water bath temperature to 70°C, and evaporate the solvent at 450rpm; then place the solid in a quartz boat, and continuously pass 100ml / min 5% H2 / Ar reducing gas was used, and then the temperature was raised to 700°C at a heating rate of 5°C / min, and high-temperature reduction was performed for 3 hours, followed by natural cooling under ventilation conditions; the catalyst was then washed with deionized water, filtered, and finally dried in an air drying oven at 70°C for 12 hours to obtain the desired catalyst.

[0053] Example 5

[0054] Dissolve dimethylglyoxime platinum complex in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, weigh 2.63g of 10wt% dimethylglyoxime platinum complex precursor solution, 0.1g NCP-50 carbon black (pre-treated by vacuum drying at 200 degrees for 24 hours) in a beaker, add 5g acetone, 0.028g 2-2-bithiophene (mass ratio of sulfur to platinum is 1:10), 50KHZ ultrasonic dispersion for 60 minutes, and stir at room temperature overnight; then transfer the mixed solution to a rotary evaporator flask, set the water bath temperature to 70°C, and evaporate the solvent at 450rpm; then place the solid in a quartz boat, and continuously pass 100ml / min 5% H2 / Ar reducing gas was used, and then the temperature was increased to 800°C at a heating rate of 5°C / min, and high-temperature reduction was performed for 2 hours, followed by natural cooling under ventilation conditions; the catalyst was then washed with deionized water, filtered, and finally dried in an air drying oven at 70°C for 12 hours to obtain the desired catalyst.

[0055] Example 6

[0056] Dissolve dimethylglyoxime platinum complex in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, weigh 2.63g of 10wt% dimethylglyoxime platinum complex precursor solution, 0.1g NCP-50 carbon black (pre-treated by vacuum drying at 200 degrees for 24 hours) in a beaker, add 5g acetone, 0.028g 2-2-bithiophene (mass ratio of sulfur to platinum is 1:10), 50KHZ ultrasonic dispersion for 60 minutes, and stir at room temperature overnight; then transfer the mixed solution to a rotary evaporator flask, set the water bath temperature to 70°C, and evaporate the solvent at 450rpm; then place the solid in a quartz boat, and continuously pass 100ml / min 5% H2 / Ar reducing gas was used, and then the temperature was raised to 900°C at a heating rate of 5°C / min, and high-temperature reduction was performed for 2 hours, followed by natural cooling under ventilation conditions; the catalyst was then washed with deionized water, filtered, and finally dried in an air drying oven at 70°C for 12 hours to obtain the desired catalyst.

[0057] Comparative Example 1

[0058] The dimethylglyoxime platinum complex is dissolved in an organic solvent to obtain a 10wt% dimethylglyoxime platinum complex precursor solution, 2.63g of the 10wt% dimethylglyoxime platinum complex precursor solution and 0.1g of NCP-50 carbon black (pretreated by vacuum drying at 200 degrees for 24 hours) are weighed in a beaker, 5g of acetone is added, the mixed solution is ultrasonically dispersed at 50KHZ for 60 minutes, and stirred at room temperature overnight; then the mixed solution is transferred to a rotary evaporator flask, the water bath temperature is set to 70°C, and the solvent is evaporated at 450rpm; then the solid is placed in a quartz boat, 100ml / min 5% H2 / Ar reducing gas is continuously introduced, and then the temperature is increased to 700°C at a heating rate of 5°C / min, high-temperature reduction is performed for 2 hours, and then the temperature is naturally lowered under ventilation conditions; then the catalyst is washed with deionized water, filtered, and finally dried at 70°C in an air drying oven for 12 hours to obtain the desired catalyst.

[0059] Comparative Example 2

[0060] Commercial TEC-10E50E was selected as comparative example 2, and its mass fraction was 50%.

[0061] Test Example 1

[0062] The catalysts of Examples 1-6 and Comparative Examples 1 and 2 were tested by X-ray diffractometer to characterize their crystal form and particle size. The results are as follows: Figure 1 , Figure 2 shown.

[0063] Depend on Figure 1It can be seen that the catalysts prepared in Examples 1-6 all showed characteristic peaks of platinum nanoparticles, indicating that platinum-carbon catalysts were successfully prepared; traditional platinum-carbon gas phase reduction generally requires a high temperature of 600-900°C or above, and a certain amount of reducing gas needs to be introduced; because it is generally carried out at normal pressure, there is a phenomenon that the reducing gas cannot contact the platinum precursor in the porous carbon, resulting in the inability to be reduced; the present invention uses a platinum complex as a precursor, and utilizes the property that the complex ligand dimethylglyoxime has reducing properties under high temperature conditions, and can completely reduce the platinum on the surface and in the pores of the porous carbon in situ, without the need to add additional gas reducing agents, the reaction conditions are simple, and the effect is better.

[0064] The peak shape of platinum characteristic peaks is different under different preparation conditions. For platinum-carbon catalysts, the sharper the platinum characteristic peaks and the greater the intensity, the larger the platinum particle size. Examples 3 and 4 have relatively wide characteristic peaks, indicating that the particle size of the platinum-carbon catalyst prepared under this process is relatively small. With the change of sulfur content and reduction temperature, the platinum particle size tends to increase, which indicates that sulfur can slow down the agglomeration of platinum nanoparticles during the gas phase preparation process, but the amount cannot be too much. If the reduction temperature is too high, the sulfur element on the carrier may be completely removed, thereby losing the function of anchoring the platinum nanoparticles. Figure 2 Comparative Example 1 is a platinum-carbon catalyst prepared without adding a sulfur-containing ligand. It can be seen from the figure that its characteristic peak is very sharp and the platinum particle size is relatively large; this shows that the addition of sulfur is very important. During the gas phase preparation process, the addition of sulfur element forms SC metal anchoring sites, which enhances the dispersion of platinum on the carrier; according to the principle of soft and hard acid and base, there is a strong interaction between the Pt-S bonds. Through the formation and elimination of the Pt-S bonds, the agglomeration and sintering of platinum nanoparticles during the heat treatment process are avoided, and the increase in their particle size is slowed down; Comparative Example 2 is a commercial catalyst with a smaller particle size.

[0065] Test Example 2

[0066] To test the activity of the embodiment and the test example, the catalyst was subjected to electrochemical performance test under the same conditions. The test method is as follows: 5 mg of the catalyst was accurately weighed into a 25 ml brown glass bottle, and 5 ml of the prepared Nafion isopropanol solution (Nafion mass fraction is 0.13%) was added; ice water ultrasonic dispersion was performed for 30 min to mix the slurry evenly; 5 μl of the dispersed slurry was transferred with a pipette, and evenly dripped onto the smooth and clean surface of the glassy carbon disk electrode, and completely dried under an infrared lamp as a working electrode; the electrode was placed in a 5-port electrolytic cell to form a three-electrode system. Among them, the reference electrode is a calomel electrode, the counter electrode is a platinum wire electrode, and the electrolyte is a 0.5 mol / L H2SO4 solution saturated with N2.

[0067] Cyclic voltammetry curve test: First, activate the catalyst for 10 cycles at a scan rate of 200mV / s in the voltage range of 0.4-1.4V (relative to reversible hydrogen (RHE) electrode), scan 4 cycles at a speed of 50mV / s, and the potential scan range is 0.05V-1.15V (relative to RHE electrode). Select the stable cyclic voltammetry curve, integrate the hydrogen desorption peak area, and then calculate the electrochemical active area ECSA of the catalyst according to the formula. The test results are as follows: Figure 3 , Figure 4 shown.

[0068] Depend on Figure 3 It can be seen that Example 3 and Example 4 have the largest electrochemical area, which are 62.1m 2 / g and 60.8m 2 / g, which shows that this process can prepare platinum-carbon catalysts with higher activity; with the change of process conditions, the electrochemical performance of the catalysts varies, especially in Example 6, whose electrochemical area is only 35.1m 2 / g, combined Figure 1 From the XRD spectrum of the catalyst, we found that the electrochemical activity of the catalyst is directly related to the size of the platinum particles. The smaller the platinum particles, the more uniformly dispersed they are on the carbon carrier with a limited area, and the higher the catalytic activity. However, when the platinum particles are large, the agglomeration phenomenon on the carbon carrier is aggravated, and the activity is reduced. For the comparative example, the particle size of comparative example 1 is larger, so its catalytic activity is very poor, which is 25.8 m 2 / g, after adding a certain amount of sulfur ligand in the embodiment, during the high-temperature reduction process, sulfur plays a strong anchoring role on the platinum metal atoms, which can effectively prevent the agglomeration of metal atoms during the preparation process and improve the catalyst activity to a certain extent; Comparative Example 2 is a commercial catalyst with better catalytic activity of 65.2m 2 / g, close to that in Example 3.

[0069] Test Example 3

[0070] In order to verify the durability of the catalyst prepared by the process of the present invention during operation, the electrolyte accelerated aging test was performed on Example 3 and Comparative Examples 1 and 2; the experimental conditions were: 0.5 mol / L H2SO4 solution was selected, the temperature was 25°C, and after high-purity N2 was used to drive out the gas for 30 minutes, a 0.6V0.95V square wave cycle was set, 0.6V stayed for 3 seconds, then stepped to 0.95V, stayed for 3 seconds, 6s / circle, a total of 10,000 circles of accelerated aging test, and the electrochemical decay rate was calculated. The experimental results are as follows Figure 5 , Figure 6 and Figure 7 shown.

[0071] It can be seen from the test results that after 10,000 cycles of accelerated aging, the catalysts all have a certain activity decay. This is because under the action of a certain amount of constant potential, the platinum on the carrier undergoes platinum dissolution, migration and other phenomena, resulting in a decrease in catalytic activity. After 10,000 cycles of accelerated aging, the decay rates of Example 3, Comparative Example 1 and Comparative Example 2 are 35.8%, 58.2% and 60.8% respectively, indicating that the catalyst prepared by the process of the present invention has excellent durability. This is because the present invention uses porous carbon and is subjected to vacuum high temperature treatment. The suitable pore structure is conducive to the diffusion of the metal precursor, and after using a small molecule solvent, the metal precursor can be evenly distributed on the surface of the carrier and in the pores, and the proportion of platinum in the pores is relatively large. In the accelerated aging process, the pores can play a certain limiting role, and the anchoring effect of sulfur on the carrier improves the durability of the catalyst; although Comparative Example 2 has a higher initial activity, it has not been subjected to high temperature heat treatment, the platinum particle size is small, and most of it exists on the surface of the carrier, and then the decay rate is large during the accelerated aging process.

Claims

1. A method for preparing a catalyst for a fuel cell, characterized in that: The following steps are involved: (1) dissolving a platinum complex in an organic solvent to prepare a platinum salt precursor solution; (2) mixing and uniformly dispersing a platinum salt precursor solution, porous carbon, a sulfur-containing ligand, and an organic solvent, and reacting the mixture to obtain a mixed solution; (3) removing the solvent from the mixed liquid to obtain a solid, and reducing the solid under high temperature and reducing gas to obtain the fuel cell catalyst.

2. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step (1), the platinum complex is at least one of a dimethylglyoxime platinum complex and a dimethylphosphonic acid platinum complex. The organic solvent is at least one of ethanol, isopropanol and n-propanol, The concentration of the platinum salt precursor solution is 2wt%-20wt%.

3. The method for preparing a fuel cell catalyst according to claim 2, characterized in that: The dimethylglyoxime platinum complex is obtained by using dimethylglyoxime as a ligand to react with a platinum salt to form a coordination reaction; The dimethylphosphonic acid platinum complex is a (dimethylphosphonic acid) platinum (II) hydrogenated complex.

4. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step (2), the porous carbon is any one of the following commercial carbons: NCP-50, NCP-20-HT and NCP-50HT. The sulfur-containing ligand is at least one of 2-2-bithiophene, diphenyl sulfoxide and disulfide, The organic solvent is at least one of ethanol, isopropanol, acetone and N,N-dimethylformamide; The mass ratio of the porous carbon to the organic solvent is 1:10-100, The mass ratio of platinum in the platinum salt precursor solution to sulfur in the sulfur-containing ligand is 1:1-20.

5. The method for preparing a fuel cell catalyst according to claim 4, characterized in that: In step (2), the porous carbon is pretreated before use, and the pretreatment is: vacuum drying at a drying temperature of 150-250° C. for 12-48 hours.

6. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step (2), the dispersion is carried out by ultrasonic dispersion, the frequency of the ultrasonic dispersion is 30-60KHZ, and the ultrasonic time is 30-180min.

7. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step (3), the specific steps of removing the solvent in the mixed solution to obtain a solid are: placing the mixed solution in a rotary evaporator, heating the mixed solution in a water bath to evaporate the solvent in the mixed solution to obtain a solid; The temperature of the water bath is 60-90° C., and the rotary evaporation rate of the rotary evaporator is 300-900 rpm.

8. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step (3), the solid is reduced under high temperature and reducing gas. During the reduction, the reducing gas used is a mixed gas of hydrogen and argon, wherein the volume ratio of hydrogen to the mixed gas is 5%. During the reduction process, ventilation was continued at a flow rate of 50-200 ml / min; The reduction temperature is 300-900°C, the reduction time is 0.5-3h, and the heating rate is 5-15°C / min.

9. The method for preparing a fuel cell catalyst according to claim 1, characterized in that: In step (3), the solid is reduced under high temperature and reducing gas, washed with water, and then filtered and dried to obtain the fuel cell catalyst; The drying temperature is 60-100° C., and the drying time is 2-6 hours.

10. A fuel cell catalyst prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Bifunctional modified platinum-carbon catalyst and preparation method thereof

    CN114583195A

  • Method for improving durability of platinum-based catalyst

    CN117317250A